KADAR SIANIDA DALAM SAYURAN DAN UMBI-UMBIAN DI DAERAH GANGGUAN AKIBAT KURANG YODIUM (GAKY) - Ance Mudiana; Sukati Saidin (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2001)
Cyanida Contents of Vegetables and Tubers In Areas of Iodine Deficiency Disorders.Background: Thiocyanate goitrogenic shows different ways to prevent iodium absorption by thyroid gland. Thiocyanate is a result of detocification from cyanide content in food which occurs in the body then is excreted through urine. Cyanide is generally found in cabbage, cassava, bamboo shoot, chinese cabbage and "slada air/jembak".